The widely utilized brominated flame retardant tetrabromobisphenol A (TBBPA) is a potent inhibitor of the SERCA Ca(2+) pump - Ogunbayo, Oluseye A. (Portland Press Ltd., 2007)
TBBPA (tetrabromobisphenol A) is currently the most widely used type of BFR (brominated flame retardant) employed to reduce the combustibility of a large variety of electronic and other manufactured products. Recent studies have indicated that BFRs, including TBBPA, are bio-accumulating within animal and humans. BFRs including TBBPA have also been shown to be cytotoxic and potentially endocrine-disrupting to a variety of cells in culture. Furthermore, TBBPA has specifically been shown to cause disruption of Ca(2+) homoeostasis within cells, which may be the underlying cause of its cytotoxicity. In this study, we have demonstrated that TBBPA is a potent non-isoform-specific inhibitor of the SERCA (sarcoplasmic/endoplasmic reticulum Ca(2+)-ATPase) (apparent K(i) 0.46–2.3 μM), thus we propose that TBBPA inhibition of SERCA contributes in some degree to Ca(2+) signalling disruption. TBBPA binds directly to the SERCA without the need to partition into the phospholipid bilayer. From activity results and Ca(2+)-induced conformational results, it appears that the major effect of TBBPA is to decrease the SERCA affinity for Ca(2+) (increasing the K(d) from approx. 1 μM to 30 μM in the presence of 10 μM TBBPA). Low concentrations of TBBPA can quench the tryptophan fluorescence of the SERCA and this quenching can be reversed by BHQ [2,5-di-(t-butyl)-1,4-hydroquinone] and 4-n-nonylphenol, but not thapsigargin, indicating that TBBPA and BHQ may be binding to similar regions in the SERCA.